THE EFFECT OF TEACHER MANAGERIAL AND TEACHER PERFORMANCE ON LEARNING ACHIEVEMENT OF GRADE V STUDENTS OF SDN TUAK DAUN MERAH, OEBOBO, KUPANG CITY IN THE NEW NORMAL ERA (2020/2021) - Erlyn Susana; Silvester P Taneo; Uda Geradus; Hotlif A Nope (Academic Journal of Educational Sciences, 2021)
This study aims to determine the effect of teacher managerial and teacher performance on student achievement. The research subjects were teachers and fifth grade students of SD Negeri Tuak Daun Merah, Oebobo District, Kupang City, each with 20 students. Sampling used the census technique, the data collection instrument used was a questionnaire. Based on the results of quantitative data analysis, it was obtained that a partial test for monopoly game media (X1) had a t-count value of 2,338, so there was a managerial influence of teachers on the learning achievement of fifth graders at Tuak Daun Merah State Elementary School, Oebobo District, Kupang City. Teacher performance (X2) obtained a t-count value of 4.558, so that there is an influence of teacher performance on the learning achievement of fifth grade students of SD Negeri Tuak Daun Merah, Oebobo District, Kupang City. F test obtained F count is 19.453, so that there is an influence of teacher managerial and teacher performance on the learning achievement of fifth grade students of SD Negeri Tuak Daun Merah, Oebobo District, Kupang City. The value of the coefficient of determination of 0.660 is equal to 66.0%. So that teacher managerial and teacher performance contribute to student learning achievement by 66.0%, while the remaining 34% (100% - 66.0%) is influenced by other variables not proposed in this study.